Effects of Neural Stem Cells combine with Nerve Growth Factor Nanoparticles Transplantation in Alzheimer's Disease Transgenic Mice - Qing ZHU; Shuai SHAO; Nan HU; Yan CHEN (康复学报)
Objective:To observe the effect of nerve growth factor(NGF)nanoparticles on the survival, migration and differentiation of transplanted neural stem cells(NSC)in the brain of APP/PS1 transgenic mice, and the effect of NSC combined with NGF nanoparticles transplantation on cholinergic neurons in basal forebrain and amyloid β-protein(Aβ)in the hippocampus and cortex.Methods:A total of 36 12-month-old male APP/PS1 transgenic mice were randomly divided into the AD control group, the NSC transplant group and the combined group, with 12 cases in each group. A total of 12-month-old wild type(WT)mice were selected as the WT control group. NSC derived from fetal brain of transgenic mice expressing enhanced green fluorescent protein(EGFP)was isolated and cultured in vitro.5 μL phosphate buffer(PBS)were injected in bilateral hippocampus of the WT control group and the AD control group, 5 μL NSC suspension and NSC combined with NGF nanoparticle suspension were injected in the bilateral hippocampus of the NSC transplant group and the combined group respectively. After transplantation for four weeks, immunofluorescence method was used to detect the survival, migration, differentiation of transplanted NSC and the change of ChAT in the basal forebrain. Real-time quantitative PCR(Q-PCR)was used to detect the mRNA expressions of ChAT and Lhx8 in the basal forebrain. Western blotting was used to detect ChAT protein expression in the basal forebrain. Thioflavine-T staining was used to detect the numbers of Aβ plaques in the hippocampus and cortex.Results:①After transplantation for four weeks, EGFP-positive NSC survived in the brain, migrated extensively to corpus callosum, cortex and deep hippocampus, and differentiated into neurons and glial cells, NSC in the combined group survived more than those in the NSC transplant group and showed more complex synaptic morphology.②The number of ChAT neurons in the basal forebrain of the NSC transplant group and the combined group increased significantly(P<0.05), compared with the NSC transplant group, the gene expression of ChAT and Lhx8 in the combined group were increased significantly(P<0.05).③The number of Aβ plaques in hippocampus and cortex of the NSC transplant group and the combined group didn't decreased significantly(P>0.05).Conclusion:NSC combined with NGF nanoparticles transplantation could indirectly protect cholinergic neurons in the basal forebrain and the survival and maturation of transplanted NSC, and promote the gene expression of ChAT and Lhx8 in the basal forebrain, but could not reduce the number of Aβ plaques in the hippocampus and cortex.